2019
DOI: 10.1038/s41388-019-0811-9
|View full text |Cite
|
Sign up to set email alerts
|

MST1R kinase accelerates pancreatic cancer progression via effects on both epithelial cells and macrophages

Abstract: The MST1R (RON) kinase is overexpressed in >80% of human pancreatic cancers, but its role in pancreatic carcinogenesis is unknown. In this study, we examined the relevance of Mst1r kinase to Kras driven pancreatic carcinogenesis using genetically engineered mouse models. In the setting of mutant Kras, Mst1r overexpression increased acinar-ductal metaplasia (ADM), accelerated progression of pancreatic intraepithelial neoplasia (PanIN), and resulted in the accumulation of (mannose receptor C type 1) MRC1+, (argi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…In a recent study by Babicky ML et al, they found that RON expression can accelerate pancreatic carcinogenesis and loss of functional RON slows progression to pancreatic cancer. They also found RON knockdown significantly inhibits tumor growth in vivo (20). In the future, we suggest that the combined detection of RON and MET in tumor tissue has better clinical value for the pathological diagnosis and prognosis evaluation in patients with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study by Babicky ML et al, they found that RON expression can accelerate pancreatic carcinogenesis and loss of functional RON slows progression to pancreatic cancer. They also found RON knockdown significantly inhibits tumor growth in vivo (20). In the future, we suggest that the combined detection of RON and MET in tumor tissue has better clinical value for the pathological diagnosis and prognosis evaluation in patients with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…RON is more meaningful as a new target of future pancreatic cancer treatment. This may be because RON can mediate oncogenic phenotypes and addiction to KRAS signaling (20). Some researchers have found that “KRAS addiction” is associated with EMT (epithelial to mesenchymal transition) and tumor cell survival (44).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also have shown that RON activation reduced the polarization of inflammatory M1 macrophages and induced the differentiation of immunosuppressive M2 macrophages. M2 macrophages promote PD-L1 expression through autocrine VEGF signaling(49,50). In our study, we demonstrate that high expression of both RON and PD-L1 (TIMC) is associated with poor overall survival in patients with CRC.…”
mentioning
confidence: 51%
“…1,2 In the case of pancreatic cancer, aberrant RON expression and signaling play a critical role in regulating cancer cells growth, invasiveness, and chemoresistance. 7,23,24,[26][27][28][29] Studies using a mouse model of K-RAS-driven pancreatic cancer further demonstrate that RON overexpression not only increases acinar-ductal metaplasia formation but also accelerates the progression of pancreatic intraepithelial neoplasia towards adenocarcinomas. 27 In breast cancer, RON activates several signaling pathways critical for proliferation, invasiveness, and stemn ess.…”
Section: Aberrant Ron Expression and Signaling In Cancer Pathogenesismentioning
confidence: 99%